Design of mini protein that mimics uricase in the preliminary development of nanowire-based uric acid biosensor - Abd Rahim, Arilla Sri Masayu (2017)
Mini protein is used as an alternative bioreceptor to native enzyme, which is costly and less stable. Mini protein that mimics enzyme may be utilized as the bioreceptor for the determination of metabolite in biological fluids. In this study, a novel uric acid biosensor of mini protein immobilized onto screen printed carbon electrodes (SPEs) was developed for uric acid detection to replace conventional method. Uricase is a large tetrameric protein carrying two active sites in each pair of dimer. This generates an interest for a mini protein to function as bioreceptor that may replace the large native enzymes. Five mini proteins comprising 20, 40, 60, 80 and 100 amino acids were designed based on the conserved active site residues within the same dimer, using the 2yzb template. Utilizing Yet Another Scientific Artificial Reality Application (YASARA) software, four target structures were predicted for each mini protein model, by multistep process of homology modeling. Then the stereochemical quality of the structure model was verified by PROCHECK and ERRAT programs. The best evaluated structures (model 3 of mp20, model 2 of mp40, model 3 of mp60, model 3 of mp80 and model 2 of mp100) were simulated with molecular dynamics (MD) simulations using YASARA, to study protein stability and folding. Five mini proteins with the highest binding energy (enzyme-substrate complex) from docking were chosen in MD simulation analysis (mini protein and the substrate). The results also proved that the present of substrate in the protein structure helped to improve protein folding. Five recombinants of mini proteins (mp20, mp40, mp60, mp80 and mp100) were constructed in pET32a vector and all of them were successfully expressed into E. coli Bl21 (DE3). The smallest mini protein with 20 amino acids (mp20) was chosen for His-tag affinity purification. The purified mp20 showed no activity in uricase assay. Subsequently, the approach was to look for binding affinity of mini protein and substrate (uric acid) via Isothermal titration calorimetry (ITC) and circular dichroism (CD) spectra. The ITC and CD results had proven that there was binding interaction between uric acid and the mini protein structure. A disposable uric acid biosensor on modified gold nanowires screen printed carbon electrode (SPEs) was fabricated. The working surface of the SPEs electrode was modified by gold nanowires deposited on the surface, followed by self-assembly of L-cysteine and glutaraldehyde. The mini protein immobilized SPEs was studied and compared to uricase immobilized SPEs as positive control. The electrocatalytic oxidation of uric acid was examined using cyclic voltammetry (CV) of a range between -1.0 and 1.0 V, at working potential 0.4 V (50 mVs-1 scan rate). The sensor demonstrated that by using mini protein as the bioreceptor, the nanowire biosensor exhibited similar stability, sensitivity, selectivity, good reproducibility and repeatability for uric acid determination, with a linear range from 0.01 mM to 1.0 mM and a detection limit of 0.1 mM as compared to control (uricase as the bioreceptor). Interestingly, the mini protein immobilized SPEs had strong affinity for uric acid compared to uricase immobilized SPEs with small value of the apparent Michaelis-Menten Constant (KM app). Besides, The mini protein immobilized SPEs had similar performance as compared to commercial uric acid biosensor in the market. In conclusion, the developed mini protein immobilized SPEs can be considered as a useful tool to replace conventional method in uric acid detection.